Selection and Design of Wind Turbine Foundation for an Offshore Wind Farm - Baoyang LI (南方能源建设, 2023)
[Introduction] From 2022, the state subsidies for offshore wind power has been fully withdrawn. The foundation of offshore wind turbines is the supporting structure of wind turbines and plays a crucial role in the safe operation of offshore wind farms. Reasonable selection and design of the offshore wind turbine foundation is an effective way to reduce costs and increase efficiency of offshore wind farms under the guidance of such policies as the "30·60" dual-carbon target and the national "14th Five-Year Plan" energy plan. [Method] The article took the selection and design of a wind turbine foundation for a certain offshore wind farm as an example, and combined the construction experience of domestic offshore wind farms to compare and select the foundation types; firstly, preliminary selection was made among three foundation types, namely monopile foundation, jacket foundation and high pile cap foundation; then, combined with the marine hydrological and geological conditions of the offshore wind farm, the applicable water depths and advantages and disadvantages of different wind turbine foundation types were analyzed, and a comprehensive comparison was conducted from the aspects of structural safety, construction feasibility, duration and engineering economy. [Result] Research has shown that the selection of wind turbine foundation type is related to several factors such as water depth, soil geological conditions, natural frequency of wind turbines, capacity of construction and equipment installation, construction duration, and engineering cost. The monopile foundation has excellent structural type, construction feasibility, the shortest construction duration and the best economy. [Conclusion] The monopile foundation is recommended for the wind turbine foundation of this offshore wind farm.